The pathogenesis of liver cancer and the therapeutic potential of bioactive substances - Gao, Song; Jiang, Xingyue; Wang, Liang; Jiang, Shanshan; Luo, Hanyuan; Chen, Yan; Peng, Cheng (Frontiers in Pharmacology, 2022)
Liver cancer is the third leading cause of cancer-related death worldwide and has become an urgent problem for global public health. Bioactive substances are widely used for the treatment of liver cancer due to their widespread availability and reduced side effects. This review summarizes the main pathogenic factors involved in the development of liver cancer, including metabolic fatty liver disease, viral infection, and alcoholic cirrhosis, and focuses on the mechanism of action of bioactive components such as polysaccharides, alkaloids, phenols, peptides, and active bacteria/fungi. In addition, we also summarize transformation methods, combined therapy and modification of bioactive substances to improve the treatment efficiency against liver cancer, highlighting new ideas in this field.